Rom, Italien. Die Villa von Sette Bassi. Geomagnetische Untersuchungen 2018 - Komp, Rainer (e-Forschungsberichte des DAI, 2020)
In the course of the project to renew the investigation of the Villa of Sette Bassi in Rome the unit for Cultural Heritage and Site Management of the German Archaeological Institute conducted a one week field campaign in order to survey the site using a multi-sensor magnetometry system. The terrain offers complex conditions due to the volcanic rock bed resulting from the Vulcano Laziale and historic contaminations (Fig. 1). Details of the central substructions in the so called hippodrome as well as adjacent buildings have been detected (Fig. 2: A. Fig. 3). A new discovery shows a road lined by columns leading towards the villa (Fig. 2: B. Fig. 4). Intense additional structures indicate the site’s further utilization, most probably in late antiquity (Fig. 2: C. Fig. 5).